2021
DOI: 10.3389/fpsyg.2021.625153
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in Motion Event Encoding Across Languages

Abstract: Syntactic templates serve as schemas, allowing speakers to describe complex events in a systematic fashion. Motion events have long served as a prime example of how different languages favor different syntactic frames, in turn biasing their speakers toward different event conceptualizations. However, there is also variability in how motion events are syntactically framed within languages. Here, we measure the consistency in event encoding in two languages, Spanish and Swedish. We test a dominant account in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…For example, Hickmann et al (2018) examined how French and English speakers expressed CM (e.g., ‘he pulled the box down the hill’) and found no difference in adult speakers’ semantic density. Similar observations have been made in comparisons between Spanish and Swedish speakers (Montero-Melis, 2021). However, these studies showed that it is also in encoding CM that speakers display more variability in their syntactic packaging strategies.…”
Section: Motion Event Typology and Language Usesupporting
confidence: 84%
See 1 more Smart Citation
“…For example, Hickmann et al (2018) examined how French and English speakers expressed CM (e.g., ‘he pulled the box down the hill’) and found no difference in adult speakers’ semantic density. Similar observations have been made in comparisons between Spanish and Swedish speakers (Montero-Melis, 2021). However, these studies showed that it is also in encoding CM that speakers display more variability in their syntactic packaging strategies.…”
Section: Motion Event Typology and Language Usesupporting
confidence: 84%
“…The seemingly superficial structural differences across languages outlined above have been found to have implications for habitual language use, particularly in terms of what aspects of motion events speakers typically profile and how often. Numerous crosslinguistic studies on motion expression have repeatedly demonstrated that S-language speakers show greater tendency to encode the framing event and the coevent simultaneously than their V-language counterparts, thereby rendering their motion descriptions semantically denser compared to those of the latter (e.g., Hendriks et al, 2021; Hickmann et al, 2009; Montero-Melis, 2021; Özçalışkan, 2015; Slobin, 2004; Tusun, 2022b; Tusun & Hendriks, 2019, 2022). The difference in semantic density has been attributed to different syntactic packaging constraints that S- versus V-languages impose on the speaker.…”
Section: Motion Event Typology and Language Usementioning
confidence: 99%
“…Tversky's (1991) survey and route descriptions). In the literature on expressing motion, individual variation is under investigated (however, see Montero-Melis et al 2017, Montero-Melis 2021. As variation is known to be related to demographic factors as well as to areal differences in language use (Berthele 2013), an interesting question is also the amount of variation that occurs beyond such factorssuch as the individual preferences and choices in language use within a demographically rather homogeneous group of subjects.…”
Section: Factors Affecting the Choice Of Formentioning
confidence: 99%
“…The factors explored relate to individual differences as well as the semantics of the motion situation and the language-specific resources for encoding motion; they are also most likely to have effects in languages in general rather than just in Finnish as discussed in this article. On the other hand, the degree of within-language variation varies between languages, as Montero-Melis (2021) shows. In his study, the Spanish event descriptions show considerably more individual variation than the Swedish ones.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more in-depth analyses have been conducted on the dimensions of motion descriptions that go beyond the general categories of path and manner (e.g. Ibarretxe-Antuñano 2017, Matsumoto & Kawachi 2020, Stosic 2020, Kopecka & Vuillermet 2021, Łozińska 2021, Montero-Melis 2021, Tuuri 2021, which significantly broadens the scope of studies of motion language.…”
Section: Introductionmentioning
confidence: 99%